A LOOK AT VERTICAL INTEGRATION FROM ORGANIZATIONAL RESOURCES AND CAPACITIES: A STUDY IN FACTORIES IN THE CLOTHING SECTOR (Desenvolvimento em Questão, 2020)
This article aims to understand the influence of strategic resources and capabilities in the choice for vertical integration in clothing factories in Maringá. To achieve the proposed objective, a qualitative and descriptive research was carried out, using semi-structured interviews with managers and partners of the clothing-making factories. With regard to the results, it was identified that, in all factories, the governance structure vertical integration is used in the modeling and creation process, a stage that constitutes the identity of these companies. The presence of contracts was also identified, mainly in the sewing stage. It was found that vertical integration, as a possible source of competitive advantage in garment factories, is influenced by strategic resources and capabilities, notably physical resources (automated cutting machine, proprietary software, proprietary physical structure), and these resources were found, mainly, in companies that are more vertically integrated. It is concluded that the factories that have a higher level of vertical integration, are also those that have more resources and strategic capabilities, potential generators of competitive advantage.
Keywords: Resource Based View. Strategic resources and capacity. Vertical Integration. Governance structures. Competitive advantage.